Effect of lubrication condition on surface roughness by using lathe machine - Rohaida, Mohd. (2008)
Cutting fluid is one of the important things in machining but it has many detrimental effects such as environmentally harmful and can cause skin and lung disease. Otherwise, cost of cutting fluid also had been issues lately because it frequently higher than cost of cutting tools and influence amount total machining cost. Because of that, dry machining and minimum quantity lubricant become alternatives to solve this problem. Objective of this project is identifying the effect of using minimum quantity lubricant compare with dry and wet machining on surface roughness. Three different materials are choosing as material test based on their hardness. There are ASTM B176 brass, AISI 1060 alloy and AISI 4340 steel. The experiment will performed under three different condition which are dry machining, minimum quantity lubricant and wet machining and will be conducted on lathe machine. After finished the experiment, it have find out that surface roughness grow slowly under minimum quantity lubricant continued by dry machining and wet machining. It means minimum quantity lubricant produced better surface finished compared with dry and wet machining. The result can significantly reduce cost and environmental pollution by using minimum quantity lubricant.